Luteolin Prevents UVB-Induced Skin Photoaging Damage by Modulating SIRT3/ROS/MAPK Signaling: An in vitro and in vivo Studies - Mu, Jing; Ma, Huisheng; Chen, Hong; Zhang, Xiaoxia; Ye, Mengyi (Frontiers in Pharmacology, 2021)
The aim of this study was to investigate the role of Luteolin in the mechanism of ultraviolet radiation B (UVB)-induced photoaging. An in vivo photoaging model was established using UVB irradiation of bare skin on the back of rats, and an in vitro photoaging model was established using UVB irradiation of human dermal fibroblasts (HDF). Skin damage was observed using hematoxylin-eosin (HE) and Masson staining, skin and cellular reactive oxygen species (ROS) levels were detected by DHE and DCF fluorescent probes, mitochondrial membrane potential was detected by JC-1 staining, and protein expressions were detected by immunofluorescence and Western Blot. Results from animal experiments showed that Luteolin reduced UVB-induced erythema and wrinkle formation. Results from cellular assays showed that Luteolin inhibited UVB-induced decrease in cell viability. In addition, in vitro and in vivo experiments showed that Luteolin reduced oxidative stress levels, decreased activation of matrix metalloproteinases (MMPs) and increased collagen expression. Continued cellular experiments using 3-TYP, an inhibitor of Sirtuin 3 (SIRT3), revealed a loss of cellular protection by Luteolin and a decrease in collagen, suggesting that Luteolin acts by targeting and promoting SIRT3. Luteolin is involved in the protection of skin cells against UVB radiation-induced ageing via the SIRT3/ROS/mitogen-activated protein kinases (MAPK) axis and it may be a promising therapeutic agent for the prevention of UVB photoaging.